The duality of network ties and attributes - Schüßler, Annabell; Fuhse, Jan (Social networks, 2025)
The article formulates an important extension of the concept of duality for network research: the duality of network ties and attributes. We transfer Breiger’s notion of the duality of cases and their attributes to network data to argue: dyads are defined by their attributes, including various kinds of relationship practices, individual traits, and combinations of traits. Conversely, the meaning of relationship practices is defined by the dyads displaying them, and by implication, by their other attributes. We illustrate the duality principle with an empirical study of sociometric nominations among 161 six-graders in eight German secondary school classes to examine: How do different kinds of ties - interpersonal relations and interest in collaborations in mathematics and physical education - relate to each other? What kinds of ties form between what kinds of school children? And how do one-sided nominations for friendship and sympathy differ from reciprocated ones? Since we do not expect monocausal relations, we conduct multiple correspondence analysis with directed ego-alter dyads as cases to explore these interrelations visually. In our analyses, school children want to collaborate with friends, and not with disliked peers. Affective ties like sympathy and friendships are chiefly same-gender and form around foci-of-activity like the neighborhood. Interest in collaborations in sports and mathematics is closely associated with interpersonal ties, but also with school grades and attributed capability in the respective subjects. Finally, one-sided nominations for friendship and sympathy indicate interpersonal ties that are weaker and less multiplex.
Online verfügbar: 11. Juli 2025
Gesehen am 28.11.2025